Empowering women and children: an empirical analysis of human development in Rome and Caltanissetta - Alba Francesca Canta (Culture e Studi del Sociale)
Amidst the various approaches that have focused on the importance of cultural processes in organising societies and institutions lies Amartya Sen’s capability approach, a multidimensional paradigm that assigns to the cultural issue a specific importance. In particular, the author relates the cultural question to the one of women, that still suffer deep discrimination, although their situation seems to have improved. The world of everyday life is structured according to a specific system of sex and gender roles, norms, habitus, beliefs, values and practices that perpetuate gender stereotypes and violence (Connell 2012). These practices, by the way, do not have an isolated impact and do not only affect women: besides being a global issue, some empirical research shows the impact of violence and discrimination on their children (Heckert et al. 2019; UNICEF 2006; Course 2006; Levendosky et al. 2003). In the wave of these studies, this contribution presents some results of research conducted in 2020 on women's empowerment and the effects on children's well-being in two Italian territories. By using mixed methodology, the results highlight the persistence of discrimination and symbolic violence the women experience in many spheres of life. To this is added the impact that such discrimination has on the well-being of children and the importance of variables such as education, health and maternal empowerment as positive factors for children’s empowerment.